The Future of Health Technology Assessment in Low- and Middle-Income Countries - Javier Guzman; Victoria Y. Fan; Peter Baker (Health Systems & Reform)
In recent decades, low- and middle-income countries (LMICs) have turned to health technology assessment (HTA) to prioritize health care interventions in pursuit of universal health coverage. HTA has demonstrated its value through significant cost savings, as shown by Thailand and Brazil, where HTA processes facilitated substantial government savings and drug price reductions. Despite these successes, many LMICs still struggle with insufficient capacity to conduct HTA or incorporate its findings into policy decisions. Only 53 percent of countries surveyed by the World Health Organization (WHO) have a legislative requirement to consider HTA results in coverage decisions. The COVID-19 pandemic highlighted the need for efficient health expenditure, prompting LMICs to seek greater value for money by investing in cost-effective interventions. To achieve this, countries will need to change the way they use HTA in the future, accounting for three important elements: agile leapfrogging past traditional HTA methodologies, aid localization to enhance country ownership and accountability, and regional collaboration to overcome common limitations such as data scarcity and limited local capacity. By addressing these elements, LMICs can optimize health spending, improve health outcomes, and ensure sustainable financing for health care systems, ultimately strengthening global health security and resilience.